Logic within the Absurdity: A Deconstructive Analysis of Edward Albee’s The Zoo Story (1959) - Zaheer, Faiza (Pakistan Languages and Humanities Review, 2023)
The major objective of this Research is to focus on the multiplicity of the interpretations in language, context, and themes of Edward Albee’s The Zoo Story (1958) while applying Jacques Derrida’s Theory of Deconstruction. The reason to apply Deconstruction to this play is to expose the American society in general and the characters in the play in particular. Characters of Jerry and Peter are the representatives of two different worlds and demonstrates opposing values to each other. This background will help the reader to understand the significance of language and diction used by these characters. This is a qualitive research as this involves different literary articles and books to expose the social chaos and psychological displacement of American society. The conclusion of this research would help the reader to explore and examine the multilayered interpretations of language used by Albee in The Zoo Story while applying the theory of Deconstruction.